BUDAYA DAERAH DALAM ERA DESENTRALISASI - Suhartono W. Pranoto (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2005)
Basically, the local culture is an asset of an ethnic group that must be maintained. It must be assumed that the cultural receivers do not neglect the high value of local wisdom. During the era of decentralization, the local culture seems to be strengthened of the state law in order to become a pin point of local enrichment. On the other hand, the local culture, that can be said as traditionalism, will stand side by side with modernism which sponsored by globalization. It means that local culture will be alive forever in the era is decentralization though external attack such globalization is going on.